Innovative Cardiopulmonary Resuscitation Training Strategy for Primary Care Staff which Addressed Pandemic Limitations: Feasibility Study for a Randomized Controlled Trial - Chalk, Mandy; Long, Tony; Miller, Amanda (International Journal of Practice-based Learning in Health and Social Care, 2025)
Primary care nurses, dental nurses, and support staff rarely attend cardiac arrest and lack crash-team support. International evidence indicates that retention of resuscitation knowledge and skills fades within the common 12-months re-training period. The primary aim was to develop and refine a new resuscitation training intervention, determining feasibility and acceptability of proposed study procedures and outcome measures. The secondary aim was to determine whether useful data should result from the main study. In a mixed-methods study, participants used a manikin with Lifesaver and QCPR resuscitation apps to determine their adult resuscitation and defibrillation skill levels. Data were recorded from the apps, observation and questionnaires. Focused interviews provided narrative data. A diverse sample was secured, and robust data resulted from data-collection activities. Participants reported procedures to be acceptable, and maintenance of skills was enhanced in the three-monthly training schedule. For the full study, minor issues of ambiguity in instructions and improved layout of the observation sheet will be corrected. Debriefing and repeated practice will be specific features. Modifications during the COVID-19 pandemic could guide essential training in similarly disruptive events. Progression criteria were exceeded. Proceeding to the statistically-powered, randomized controlled trial to establish the impact of a novel resuscitation training strategy was indicated.